Dengue Fever with pulmonary alveolar hemorrhage - Common infection with uncommon association - rare case report - Prusty, B Saroj Kumar; Momin, Majed Abdul Basit (Bangladesh Journal of Medicine, 2019)
Dengue fever (DF) is major health hazard around the world in recent decades especially in India. Flu like illness to polyserositis among common presentation of DF. Dengue fever presenting as pulmonary hemorrhage is rare. Here we present a case of 16 -year young male patient presented with fever and shortness of breath, initially diagnosed as dengue fever by serological examination. CT chest findings mimiking as pneumonia ,however further fall in hemoglobin and progressive dysnoea, bronchoscopy and bronchial wash cytology done which reveal association of pulmonary hemorrhage. This case report alerted clinicians about rare presentation and high index of suspicion of pulmonary hemorrhage in DF with dysnoea for early diagnosis and to avoid its fatal outcome. Bangladesh J Medicine Jan 2019; 30(1) : 38-40